2018
DOI: 10.1371/journal.pone.0203528
|View full text |Cite
|
Sign up to set email alerts
|

The limits of the foreign language effect on decision-making: The case of the outcome bias and the representativeness heuristic

Abstract: Language context (native vs. foreign) affects people’s choices and preferences in a wide variety of situations. However, emotional reactions are a key component driving people’s choices in those situations. In six studies, we test whether foreign language context modifies biases and the use of heuristics not directly caused by emotional reactions. We fail to find evidence that foreign language context modifies the extent to which people suffer from outcome bias (Experiment 1a & 1b) and the use of the represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 37 publications
4
38
0
Order By: Relevance
“…Indeed, Anooshian and Hertel (1994) found that participants remembered emotional words better than neutral words in their NL, but not in their FL. This is in line with foreign language effect (FLE) research supporting a reduction in emotionality in an FL (Costa, Foucart, Hayakawa, et al, 2014;Costa, Foucart, Arnon, Aparici, & Apesteguia, 2014;Costa, Vives, & Corey, 2017;Hadjichristidis, Geipel, & Savadori, 2015;Keysar, Hayakawa, & An, 2012, but see Vives, Aparici, & Costa, 2018). Conversely, other studies find the same effects of emotion on memory in both languages (Ayçiçe i & Harris, 2004;Caldwell-Harris, 2009;Ferré, Ventura, Comesaña, & Fraga, 2015;Ponari et al, 2015).…”
Section: The Influence Of Emotional and Foreign Language Context In Csupporting
confidence: 83%
See 1 more Smart Citation
“…Indeed, Anooshian and Hertel (1994) found that participants remembered emotional words better than neutral words in their NL, but not in their FL. This is in line with foreign language effect (FLE) research supporting a reduction in emotionality in an FL (Costa, Foucart, Hayakawa, et al, 2014;Costa, Foucart, Arnon, Aparici, & Apesteguia, 2014;Costa, Vives, & Corey, 2017;Hadjichristidis, Geipel, & Savadori, 2015;Keysar, Hayakawa, & An, 2012, but see Vives, Aparici, & Costa, 2018). Conversely, other studies find the same effects of emotion on memory in both languages (Ayçiçe i & Harris, 2004;Caldwell-Harris, 2009;Ferré, Ventura, Comesaña, & Fraga, 2015;Ponari et al, 2015).…”
Section: The Influence Of Emotional and Foreign Language Context In Csupporting
confidence: 83%
“…However, the use of emotional semantic contexts can be a short-term tool in the classroom, particularly during aural exercises or verbal transmission of new information in order to boost memory. Considering the emotional distancing or detachment that has been typically associated with FL contexts (see Costa et al, 2018), the use of emotionally loaded materials or activities in classroom settings could be useful for partially counteract existing FLEs. Note: Numbers in parentheses refer to standard deviation for the FL and NL groups, except for in the final line (Bayes Factor) where they refer to error percentage.…”
Section: Resultsmentioning
confidence: 99%
“…One is that several works have shown that information processed in a second language does not increase analytic thinking. For example, foreign language does not improve performance on CRT (Costa et al, 2014a), conjunction fallacy or base rate neglect problems (Vives et al, 2018), and detection of semantic illusions (Geipel et al, 2015; but see Hadjichristidis, Geipel, & Surian, 2017). Therefore, if anything, foreign language can be a useful technique to impair Type 1 thinking, but not to promote Type 2 responses.…”
Section: Conceptual Primingmentioning
confidence: 96%
“…According to the reduced emotionality account, our emotions have a stronger impact on our decision-making processes when we think in our native language as opposed to our non-native language (Keysar et al, 2012;Corey et al, 2017;Hayakawa et al, 2017;Vives et al, 2018;Hadjichristidis et al, 2019a). Since emotions might play into certain heuristics or biased reasoning, reducing emotion by actively thinking in a non-native language would allow for reasoning that is not interrupted or distorted by emotional reactions that one would have experienced reasoning in L1.…”
Section: The Reduced Emotionality Accountmentioning
confidence: 99%